The collaborative research and education system on poultry and eggs (CRESCOVA) to achieve balanced nutrition and prevent stunting - Rachmy Rosyida Ro’is; Deviany Hanadia Nuryalestri; Naifa Inggit Kheisya Putri; Sifa Indriani (Public Health Risk Assesment Journal, 2026)
Background: Stunting remains one of Indonesia’s most critical public-health challenges, affecting child growth, cognitive development, and long-term human-capital productivity. Despite national efforts to accelerate stunting reduction, gaps persist in dietary diversity, nutrition literacy, and integration between health and agricultural sectors. Poultry and eggs—nutrient-dense, affordable, and widely acceptable—represent a strategic yet underutilized entry point for improving child nutrition. This study aims to synthesize interdisciplinary evidence and develop the CRESCOVA (Collaborative Research and Education System on Poultry and Eggs) framework as an innovative model that integrates nutrition education, small-scale poultry practices, and community empowerment to support Indonesia’s stunting-reduction agenda. Method: This research employed a qualitative descriptive literature-review design. A systematic search was conducted across Scopus, PubMed, Web of Science, ScienceDirect, DOAJ, Google Scholar, FAO, WHO, UNICEF, World Bank, Kemenkes, and BKKBN repositories (2019–2025), supplemented with foundational meta-analyses. A total of 52 eligible sources were analyzed using narrative thematic synthesis, covering nutrition-sensitive agriculture, animal-source foods, community-based education, and cross-sector collaboration. Extracted themes were integrated to construct the CRESCOVA conceptual model and validated against national policies and global development frameworks. Finding: Results show consistent evidence that egg and poultry consumption significantly improves linear growth and dietary adequacy among children, while participatory nutrition education enhances caregiver behavior. Cross-sector interventions linking health, education, and agriculture demonstrate greater impact than fragmented programs. Based on these findings, the CRESCOVA model offers a scalable, context-appropriate framework that strengthens household capacity, promotes women’s empowerment, and aligns with SDG 2 and SDG 3 to improve food security and child nutrition outcomes. Conclusion: CRESCOVA provides a practical strategy to operationalize multisectoral stunting-reduction efforts through integrated education and poultry-based learning. Further field implementation and evaluation are recommended to assess feasibility across Indonesia’s diverse regions. Novelty/Originality of this article: This study introduces the CRESCOVA framework as a novel socio-technical intervention that specifically bridges the gap between nutrition-sensitive agriculture and public health education in the Indonesian context.